Key implications on food storage in cold chain by energy management perspectives - Karacan, M. Akif; Yilmaz, I. Cengiz; Yilmaz, Deniz (Frontiers in Sustainable Food Systems, 2023)
Over the past decades, increase in food shortages and food costs with the drought caused by population growth and climate change, it becomes more important to prevent food losses with the widespread use of cold storage. That's why many countries provide incentives for the widespread use of cold stores. However, with cold storages becoming more widespread, keeping energy consumption under control becomes an important issue. Especially in most developing countries, the status and energy performance of installed cold stores are unknown. In this study, energy consumption data were examined by using data from cold stores from different countries. The relationships between some parameters (capacity, volume, etc.) affecting energy consumption were analyzed for 67 established cold stores. In order to measure the energy consumption data of the system under ideal operating conditions, experiments were carried out in the test room under laboratory conditions and comparisons were made according to the data obtained from the field. The data obtained showed that energy consumption in cold stores increased by up to 30%, depending on operating conditions. Therefore, it is very important that cold stores are inspected by the relevant institutions after they are established and during their operation.